Semantic Analysis and Spectrum Modelling Approach for Hand Written English Text Recognition using Neural Network (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One of the most common sources of writing media in ancient times was handwritten notes.One of the most natural ways to write characters is through handwriting. A Japanese brush pen is a popular writing instrument that is used in school for practising writing characters.One of the most common degrading factors that influence image visibility and makes them unclear is noise. Pepper salt noise, speckle noise, and holes on billings, for instance, seem to be the most prominent noises found in manuscripts. There are many denoising methods available. We surveyed the literature from both basic and advanced algorithms in this paper.